A study of age as a risk factor in ischemic stroke of elderly - Reddy, Hari Priya; A., Jaganath; N., Nagaraj; Y. J., Visweswara Reddy (International Journal of Research in Medical Sciences, 2019)
Background: The aim of the study was to determine the effect of age as a risk factor and a determinant of outcome in elderly ischemic stroke patients. Methods: This is an observational study. One hundred, successive elderly patients aged 60 years and above, admitted with acute ischemic stroke in PESIMSR over a period of 18 months were prospectively studied. Patients with hemorrhagic stroke, neurological deficits following trauma or following infection were excluded. Demographics, risk factors, stroke severity at admission were estimated by NIHSS. Risk factors and clinical profile were noted and compared among male and female patients. Outcome at discharge was measured by-mRS-modified ranking score. Results: Patients in age group 60-75 years presented with less severe stroke and better mRS when compared to >75 years age group. Complications were significantly higher among the older age group. Conclusions: The risk factors identified for ischemic stroke in the present study are diabetes, hypertension, dyslipidaemia, obesity, smoking, and alcohol. Severity of stroke at presentation, clinical outcome and complication rate during the in-hospital stay were all significantly affected by the age, more so in ischemic stroke. Age specific factors of stroke prevention are crucial for successful prevention and implementation of well-organized stroke care.